2017
DOI: 10.1136/bmjdrc-2016-000352
|View full text |Cite
|
Sign up to set email alerts
|

Preserved glucagon-like peptide-1 responses to oral glucose, but reduced incretin effect, insulin secretion and sensitivity in young Asians with type 2 diabetes mellitus

Abstract: ObjectiveYouth onset type 2 diabetes mellitus (YT2DM) is a globally rising phenomenon with substantial Asians representation. The understanding of its pathophysiology is derived largely from studies in the obese African-American and Caucasian populations, while studies on incretin effect are scarce. We examined the insulin resistance, β-cell function (BC), glucagon-like peptide (GLP)-1 hormone and incretin effect in Asian YT2DM.Research design and methodsThis case–control study recruited 25 Asian YT2DM and 15 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 37 publications
1
22
3
Order By: Relevance
“…Further studies are needed to understand if there were subtypes of T2D with different pathophysiology necessitating different treatment approach. Asian youths with T2D have preserved glucagon-like peptide-1 response to oral glucose, but decreased incretin effect, beta-cell function and insulin sensitivity [25]. Further studies are needed to elucidate the possibility of GLP-1 resistance in youth with T2D and role of incretin-based therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies are needed to understand if there were subtypes of T2D with different pathophysiology necessitating different treatment approach. Asian youths with T2D have preserved glucagon-like peptide-1 response to oral glucose, but decreased incretin effect, beta-cell function and insulin sensitivity [25]. Further studies are needed to elucidate the possibility of GLP-1 resistance in youth with T2D and role of incretin-based therapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is necessary to be cautious with this upregulation of incretins in response to high-sugar diets, because it has been described that in diabetic patients, who have increased levels of incretins, a reduced incretin effect is observed, which suggest the development of an "incretin resistance" process [280][281][282][283].…”
Section: Impact Of Excessive Dietary Sugars Consumption On Incretin Smentioning
confidence: 99%
“…A study from Malaysia in subjects with young-onset T2DM and healthy control showed that Asian young-onset T2DM showed similar GLP-1 response to oral glucose as a control but reduced incretin effects, beta cell functions, and insulin sensitivity. The peak GLP-1 levels were observed at 15 minutes in both groups [13]. Study on GLP-1 levels during 75 g glucose loading in a Japanese population with normal glucose tolerance showed that GLP-1 levels increased post glucose loading from fasting state and the peaked levels was observed at 60 minutes and declined until the end of observation at 180 minutes [14].…”
Section: Discussionmentioning
confidence: 99%